PENGARUH PERENCANAAN STRATEGI BISNIS TERHADAP KINERJA USAHA KECIL MENENGAH YANG DIMEDIASI STRATEGI KEUNGGULAN KOMPETITIF - Fatchuroji, Acep; Sabihaini, Sabihaini; Sutiono, Heri Tri (Jurnal Ilmu Administrasi dan Bisnis, 2020)
The purpose of this study is to determine the role of competitive advantage in mediating the effect of business strategy planning on SME performance. The research sample of 139 SMEs using proportional cluster random sampling techniques were tested using AMOS structural equation modeling (SEM) analysis. The results showed that the business strategy planning implemented by SMEs was formal business strategy planning, where the application of increasingly formal business strategy planning was able to improve the performance of SMEs and be able to provide a competitive advantage for SMEs. SMEs need to carry out a gradual evaluation and submit their ideas to the members so that the performance of SMEs can be achieved in line with expectations. SMEs need to be more mature in planning business strategies that will be taken, sorting out the advantages of what is owned and not owned by competitors where this will provide its own value for SMEs. The suitability of the plan and strategy chosen can provide better performance than before.